Urban Traffic Simulators - Harshita Chitla H (International Journal of Informatics and Communication Technology (IJ-ICT), 2016)
Computer traffic simulation is a widely used technique in modeling, coming up with and development of traffic networks and systems. It contains a various applications, like traffic forecasting, vehicle navigation devices and so on. This paper discusses about the various types of traffic simulators. Another drawback is that the factors like accidents, public events, and road closures. In addition, we are introducing algorithmic concepts, quantifiable metrics and data structural approaches that might be applied to the simulation systems.